[Mingling at the groundbreaking] - P. K. Phillips::::::photographer::: (1978)
A Congregation of people standing near the lawn across from the main entrance to the library. This gathering presumably has to do with the opening and/or commemoration of Kennedy Library. The Walter F. Dexter Building (Building 34) is in the background.